Designing of a Personality Based Emotional Decision Model for Generating Various Emotional Behavior of Social Robots. (5th January 2014) - Ahn, Ho Seok
Abstract : All humans feel emotions, but individuals express their emotions differently because each has a different personality. We design an emotional decision model that focuses on the personality of individuals. The personality-based emotional decision model is designed with four linear dynamics, viz. reactive dynamic system, internal dynamic system, emotional dynamic system, and behavior dynamic system. Each dynamic system calculates the output values that reflect the personality, by being used as system matrices, input matrices, and output matrices. These responses are reflected in the final emotional behavior through a behavior dynamic system as with humans. The final emotional behavior includes multiple emotional values, and a social robot shows various emotional expressions. We perform some experiments using the cyber robot system, to verify the efficiency of the personality-based emotional decision model that generates various emotions according to the personality.